KEBIJAKAN REGULASI BAITUL MAAL WAT TAMWIL (BMT) DI INDONESIA - Mursid, Fadillah (Nurani, 2018)
KEBIJAKAN REGULASI BAITUL MAAL WAT TAMWIL (BMT) DI INDONESIA Fadillah Mursid Abstract The financial sector in Indonesia is one of the sectors that has an important role in encouraging the improvement of the national economy and the economy of society. then, of course, institutions or agencies involved in the financial sector require clear regulation as the rules of the game. Ironically BMT as one of the micro-finance institutions actually tend to receive less attention from the government, especially regarding the regulation. Whereas regulation is one of the most important factors that affect sustainability BMT. Departing from the background, this study aims to know, examine and explain how the regulation of Baitul Maal Wat Tamwil (BMT) in the Regulations of Cooperatives Cooperatives, the Foundation Act, and the Law of Microfinance Institutions as well as why the existing BMT regulatory policy like today? This research including the kind of research normative law, while specification this research is descriptive analytical Legal material used in covering primary, secondary, and tertiary legal materials. The collection of legal materials in this paper is done by doing literature research and document studies. The main approach is doctrinal. Based on the results of research that the authors do can be summarized as follows: 1. The arrangement of BMT with the Law of Cooperatives is only temporary until the issuance of the Act specifically regulate the issue of BMT. 2. The foundation law can not be used as the basis of BMT regulation, because the foundation is an institution that is only oriented to social interests, while BMT has a social function as well as profit oriented. 3. The regulation of BMT in Act No. 1 of 2013 on Microfinance Institutions has provided clarity on what and how should BMT institutional, sharia aspect guidance, supervision and guarantee of customer's savings, although until now there is a Government Regulation which regulates further how to guarantee mechanism of deposit in micro financial institution especially BMT. 4. Current BMT regulatory policies tend to encourage the development of BMTs towards financial institutions such as banks. Keywords: Policy, Regulation, BMT, Indonesia Abstrak Sektor keuangan di Indonesia merupakan salah satu sektor yang memiliki peranan penting dalam mendorong peningkatan perekonomian nasional dan ekonomi masyarakat. maka, sudah barang tentu lembaga atau instansi yang berkecimpung di sektor keuangan memerlukan regulasi yang jelas sebagai aturan mainnya. Ironisnya BMT selaku salah satu lembaga keuangan mikro justru cenderung kurang mendapat perhatian dari pemerintah khususnya mengenai regulasinya. Padahal regulasi merupakan salah satu faktor paling penting yang mempengaruhi sustainabilitas BMT. Berangkat dari latar belakang tersebut, penelitian ini bertujuan untuk mengetahui, mengkaji dan menjelaskan bagaimana regulasi Baitul Maal Wat Tamwil (BMT) dalam Peraturan Perundang-Undangan Perkoperasian, Undang-Undang Yayasan, dan Undang-Undang Lembaga Keuangan Mikro serta mengapa kebijakan regulasi BMT yang ada seperti saat ini? Penelitian ini termasuk jenis penelitian hukum normatif, sedangkan spesifikasi penelitian ini adalah deskriptif analitis. Bahan hukum yang digunakan dalam meliputi bahan hukum primer, sekunder, dan tersier. Pengumpulan bahan hukum dalam penulisan ini ditempuh dengan melakukan penelitian kepustakaan dan studi dokumen. Pendekatan utama yang ditempuh adalah doktrinal. Berdasarkan dari hasil penelitian yang penulis lakukan dapat disimpulkan sebagai berikut: 1. Pengaturan BMT dengan Undang-Undang Perkoperasian hanya bersifat sementara sampai dikeluarkannya Undang-Undang yang secara spesifik mengatur persoalan BMT. 2. Undang-Undang yayasan tidak bisa dijadikan dasar pengaturan BMT, dikarenakan yayasan merupakan lembaga yang hanya berorientasi pada kepentingan sosial, sedangkan BMT memiliki fungsi sosial sekaligus profit oriented. 3. Pengaturan BMT dalam Undang-Undang nomor 1 tahun 2013 tentang Lembaga Keuangan Mikro telah memberikan kejelasan tentangi apa dan bagaimana seharusnya kelembagaan BMT, pedoman aspek syariah, pengawasan, dan penjaminan simpanan nasabah, meskipun sampai saat ini belam ada Peraturan Pemerintah yang mengatur lebih lanjut bagaimana mekanisme penjaminan simpanan dalam lembaga keuangan mikro khususnya BMT. 4. Kebijakan regulasi BMT saat ini cenderung mendorong perkembangan BMT ke arah lembaga keuangan seperti halnya perbankan. Kata Kunci: Kebijakan, Regulasi, BMT, Indonesia